Synthesis of 4-Quinolones through Nickel-Catalyzed Intramolecular Amination on the β-Carbon of o-(N-Alkylamino)propiophenones - Ueno, Satoshi; Shimizu, Ryosuke; Maeda, Ryohei; Kuwano, Ryoichi (Synlett, 2012)
o-(N-Alkylamino)propiophenones are converted into 4-quinolones in the presence of chlorobenzene, potassium phosphate, morpholine, and nickel(0) catalyst. The reaction proceeds through the nickel-catalyzed formation of β-enaminones from o-(N-alkylamino)propiophenones and morpholine, followed by the intramolecular transamination.
Keywords: nickel; cyclization; amination; ketones; oxidation